The Songs of Their Fathers - Whidden, Lynn (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2003)
Abstract This article is based upon a corpus of thirty-three songs sung by Métis women in the Red River area during the late nineteenth and twentieth centuries. The author focuses mainly on the song lyrics to understand the thoughts and concerns of Métis women as they adjusted to life in non-Native society and explores the adoption of, and love for folksong that is part of the French Canadian tradition.